Metaheuristic Optimization in Power Engineering: Algorithms and Power Dispatch Using MATLAB®-Based Software, Volume 1 - Radosavljevic, Jordan (Energy Engineering, 2024)
A new edition in two volumes of the systematic and comprehensive reference on metaheuristic methods for power systems with distributed renewables, which offers MATLAB-based software, with revised and new chapters.